Proceedings of the 41st International Conference on Advanced Ceramics and Composites. Ceramic engineering and science proceedings. Volume 38, issue 3, 2017 : a collection of papers presented at the 41st International Conference on Advanced Ceramics and Composites January 22-27, 2017, Daytona Beach, Florida - International Conference on Advanced Ceramics and Composites 2017 : Daytona Beach, Fla.); Kriven, Waltraud M.; Bansal, Narottam P.; Kusnezoff, Mihails; Ohji, T. (Tatsuki); Zhou, Yanchun; Il Moon, Kyoung; Matyáš, Josef; Shimamura, Kiyoshi; Kirihara, Soshu; Gupta, Surojit; Wang, Jingyang (Materials scientist) (Hoboken, NJ : Wiley, 2018)
This proceedings contains a collection of 23 papers from The American Ceramic Society s 41st International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 22-27, 2017. This issue includes papers presented in the following symposia: Symposium 1 Mechanical Behavior and Performance of Ceramics and Composites Symposium 2 Advanced Ceramic Coatings for Structural, Environmental, and Functional Applications Symposium 4 Armor Ceramics: Challenges and New Developments Symposium 5 Next Generation Bioceramics and Biocomposites 6th Global Young Investigators Forum.
Online resource; title from PDF title page (EBSCO, viewed January 24, 2018).
Includes bibliographical references.
Keywords: Ceramic materials -- Congresses; Electric insulators and insulation -- Ceramic materials -- Congresses; Insulation (Heat) -- Congresses; Detectors -- Materials -- Congresses; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Ceramic materials; Detectors -- Materials; Electric insulators and insulation -- Ceramic materials; Insulation (Heat); Electronic books; Conference papers and proceedings